Impact of chronic kidney disease on quality of life, lung function, and functional capacity - Carolina Guimarães Teixeira; Maria do Carmo M.B. Duarte; Cecília Maciel Prado; Emídio Cavalcanti de Albuquerque; Lívia B. Andrade (Brazilian Society of Pediatrics, 2014)
Objectives: To evaluate the impact of the chronic kidney disease (CKD) on quality of life, from the children's and their parents' perspective, respiratory muscle strength, lung function, and functional capacity in children and adolescents. Method: Cross‐sectional study of children with CKD aged 8 to 17 years. Those incapable of taking the tests were excluded. After an interview, quality of life by Pediatric Quality of Life Inventory) (PedsQLTM), muscular strength, pulmonary function tests, and the 6‐minute walking test (6MWT) were applied. Student's t‐test, ANOVA (difference in means), and Pearson's coefficient of correlation were used. The level of significance was set at 5%. Results: Of the 40 patients, the mean distance walked at the 6MWT was 396 meters, and the mean final score at the quality of life test as perceived by the children and parents was 50.9 and 51, respectively. From the children's perspective, the transplanted patients had a higher quality of life score when compared to those undergoing hemodialysis (p < 0.001); those who practiced physical activity had better quality of life when compared to the sedentary children (p < 0.001). From the children's and the parents' perspectives, the male gender had a higher quality of life score (p < 0.05). There was a positive correlation between the distance walked at the 6MWT and age, height, final PedsQLTM, forced vital capacity (FVC), and forced expiratory volume in the first second (FEV1), as well as a negative correlation between FEV1/FVC and the distance walked. Conclusion: A significant reduction in the quality of life and the functional capacity was observed in children with CKD, influenced by the type of treatment, gender, and sedentary life style.